2011
DOI: 10.1007/s11250-011-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper edetate injection in dry pregnant cows on hematology, blood metabolites, weight gain and health of calves

Abstract: The objectives of the present study was to investigate the effects of the copper injection and injection timing to pregnant dairy cows at dry period on the hematology, some serum metabolites, health and growth of their calves. Thirty Holstein cows at the dry period were assigned to the three following experimental groups: 1) control (injections of 2.5 ml normal saline), 2) test 1 (125 mg Cu as copper edetate injection at the first week of the dry period) and 3) test 2 (125 mg Cu as copper edetate injection at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
4
0
2
Order By: Relevance
“…It is thought that this situation in the treatment group results from the administration of minerals regarding carbohydrate metabolism such as mangan (Abdelrahman and Kincaid 1993). For the control group, high glucose levels measured during the intrapartum period, as compared to the prepartum and postpartum values, agree with the previous reports that blood glucose levels increase during the intrapartum period (Ghergariu et al 1984, Park et al 2010, Hesari et al 2012.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is thought that this situation in the treatment group results from the administration of minerals regarding carbohydrate metabolism such as mangan (Abdelrahman and Kincaid 1993). For the control group, high glucose levels measured during the intrapartum period, as compared to the prepartum and postpartum values, agree with the previous reports that blood glucose levels increase during the intrapartum period (Ghergariu et al 1984, Park et al 2010, Hesari et al 2012.…”
Section: Discussionsupporting
confidence: 89%
“…Tothova et al (2008) stated that in postpartum period, the serum TP and ALB levels were low as compared to the prepartum and parturient periods. Hesari et al (2012) noted that copper additions did not cause any damage in the ALB rates in lactating cows. Ucar et al (2011) stated that CRSC and ALB levels remained unchanged in cows receiving mineral solution.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, some minerals such as Se, Cu, Zn [25], and Fe [26], the main cofactors in antioxidation, are pivotal to enhance the immune system and prevent oxidative stress. Moreover, the roles of minerals in growth [27,28], feeding and digestion [18,29], and reproduction [30,31] in ruminants are well established, but this research has mainly been done on cattle. In sheep, it has been reported that adding water to TMR during THE and water deprivation does not change serum biochemical and hematologic parameters or circulating hormone levels [16,22].…”
Section: Mineralsmentioning
confidence: 99%
“…Hem kontrol hem de deney grubunda doğum öncesi ve sonrası değerlere nazaran doğum anında saptanan yüksek glikoz düzeyleri, doğum sırasında kan glikoz düzeylerinin yüksel-diğini bildiren araştırıcıların 30,32,33 bulgularıyla da uyumlu bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified
“…Doğumdan sonraki süreçte serum total protein ve albumin düzeyleri doğum öncesi ve sonrası dönemlere kıyasla düşük olduğu bir çalışmada saptanmış-tır 39 . Başka bir araştırmada bakır ilavelerinin laktasyondaki ineklerde albümin oranlarında bir değişime neden olmadığı saptanmıştır 32 . Ucar ve ark.…”
Section: Tartişma Ve Sonuçunclassified